RAPSODI MAHOGANI DALAM PEMAHAMAN LINTAS BUDAYA SERUMPUN - Puji Santosa (Widyaparwa, 2011)
Makalah ini membahas novel Rapsodi Mahogani karya Rosli Abidin Yahya dalam pemahaman lintas-budaya, yaitu pemahaman budaya pembaca yang berasal dari Jawa (Indonesia) untuk memahami budaya Melayu (Brunei Darussalam) yang tercermin dalam novel Rapsodi Mahogani. Lintas-budaya dipahami sebagai sebuah pertemuan antara dua atau lebih budaya yang berlangsung dengan cepat. Pertemuan dua budaya dapat menyebabkan gagap budaya. Hal ini disebabkan oleh kurangnya pemahaman konvensi bahasa dan konvensi budaya dari novel yang dibaca. Novel Rapsodi Mahogani ditinjau dari segi konvensi bahasa terdapat banyak kosa kata Melayu yang dianggap arkais dan untuk memahami maknanya perlu membuka kamus. Ditinjau dari segi konvensi budaya, novel Rapsodi Mahogani tidak mencerminkan kekhasan budaya Melayu yang saleh mengerjakan agama Islam dengan baik. Bahkan, dalam novel ini terasa jauh mengimpor budaya Barat, terutama Yunani dan Inggris. Sebagai hasil dari pertemuan budaya Barat, yang identik dengan budaya modern, dengan budaya Timur, yang masih irasional dan alami, perdaban budaya adat atau budaya lokal setempat menjadi musnah atau hancur.This paper discussed about Rapsodi Mahogani, a novel by Rosri Abidin Yahya in intercultural understanding of reading habit understanding of readers from Java (lndonesia) to understand Malay culture (Brunei Darussalam) as reflected in the "Rapsodi Mahogani". The intercultural was understood as a fast meeting point of one or more culture. The two meeting culture could make cultural distortion understanding. lt was caused by the lack of language and cultural convention understanding from the novel read. The "Rapsodi Mahogani" when was reviewed from language convention showed many Malay archaic vocabulary. To understand those vocabularies meaning, then, it was needed dictionary. Reviewed from cultural convention, the "Rapsodi Mahogani" did not reflect specific Malay culture that was identical with obeying in Islam religious service. The novel, even, seemed importing Western culture, particularly Greek and England. As result of Western culture meeting which was identical with modernity and Eastern culture which was still irrational and natural, traditional cultural civilization or local culture became eliminated or ruined.